Size and charge antigens of Dirofilaria immitis adult worm for IgG-Elisa diagnosis of bancroftian filariasis (Southeast Asian Journal of Tropical Medicine and Public Health, (2010), 41, 2, (285)) - Riyong D. (2014)
[No abstract available]